Mind - Searle, John R. (Oxford University Press, 2004)
The philosophy of mind is unique among contemporary philosophical subjects, writes John Searle, "in that all of the most famous and influential theories are false." One of the world's most eminent thinkers, Searle dismantles these theories as he presents a vividly written, comprehensive introduction to the mind. He begins with a look at the twelve problems of philosophy of mind--which he calls "Descartes and Other Disasters"--problems which he returns to throughout the volume, as he illuminates such topics as materialism, consciousness, the mind-body problem, intentionality, mental causation, free will, and the self. The book offers a refreshingly direct and engaging introduction to one of the most intriguing areas of philosophy